THz radiation based on femtosecond electron bunches and THz imaging - Saisut J. (2017)
The THz radiation from femtosecond electron bunches is focused on a sample which will be scanned using an xy-translation stage. The transmission intensity at different points of the sample are detected to construct a THz image. THz images of some samples were demonstrated using the THz imaging system.